NILAI SOSIAL ANTOLOGI PUISI “NGEPAK-NGEPAK” KARYA FAHRURRAJI ASMUNI: KAJIAN HERMENEUTIKA GADAMER (SOCIAL VALUES OF THE POETRY ANTHOLOGY "NGEPAK-NGEPAK" BY FAHRURRAJI ASMUNI: A STUDY OF GADAMER'S HERMENEUTICS) - Setiawan, Deddy Andria (JURNAL BAHASA, SASTRA, DAN PEMBELAJARANNYA, 2024)
AbstractSocial Values of the Poetry Anthology "Ngepak-Ngepak" by Fahrurraji Asmuni: A Study of Gadamer's Hermeneutics. This research is motivated by the importance of gaining a better understanding of the social value contributions of the poetry anthology "Ngepak-Ngepak" in its social context. The study also has the potential to provide new insights into how poetry can convey socially relevant messages to society. The aim of this research is to interpret the social values contained in the poetry anthology titled "Ngepak-Ngepak" by Fahrurraji Asmuni through Gadamer's hermeneutics, focusing on understanding cultural context, symbolic meanings, and subjective individual experiences. The research method used is qualitative analysis of the poetry text. The data obtained is analyzed using Gadamer's hermeneutic approach, which involves a dialectic between the reader's horizon and the text's horizon in order to provide a more comprehensive interpretation of the social values contained in the poetry. The social values conveyed by the poet through the understanding of the dominant cultural context indicate vital values, while those based on their sources predominantly demonstrate values of affection. The social values derived from the interpretation of symbolic meanings indicate vital and spiritual values, while those based on their sources demonstrate values of affection, life harmony, and responsibility. The social values derived from the subjective experiences of the readers indicate vital and spiritual values, while those based on their sources demonstrate values of affection, life harmony, and responsibility. Fahrurraji Asmuni's work remains relevant to contemporary life and can serve as a guide for us in navigating life.Keywords: sociology of literature, social values, hermeneutics, poetry, horizonAbstrakNilai Sosial Antologi Puisi “Ngepak-Ngepak” Karya Fahrurraji Asmuni: Kajian Hermeneutika Gadamer. Penelitian ini dilatarbelakangi oleh pentingnya memberikan pemahaman yang lebih baik tentang kontribusi antologi puisi "Ngepak-Ngepak" dalam konteks nilai sosial. Penelitian ini juga berpotensi memberikan wawasan baru tentang cara puisi dapat menyampaikan pesan-pesan sosial yang relevan dengan masyarakat. Penelitian ini bertujuan untuk menginterpretasi nilai sosial yang terkandung dalam antologi puisi berjudul "Ngepak-Ngepak" karya Fahrurraji Asmuni dengan  kajian hermeneutika Gadamer melalui pemahaman konteks budaya, makna simbolik, dan pengalaman subjektif individu. Metode penelitian yang digunakan adalah analisis kualitatif terhadap teks puisi. Data yang diperoleh dianalisis menggunakan pendekatan hermeneutika Gadamer yang melibatkan dialektika antara horizon pembaca dengan horizon teks agar dapat memberikan interpretasi yang lebih komprehensif dalam memahami nilai-nilai sosial yang terkandung dalam puisi. Nilai sosial yang disampaikan penyair melalui pemahaman konteks budaya dominan menunjukkan nilai vital sedangkan berdasarkan sumbernya dominan menunjukkan nilai kasih sayang. Nilai sosial dari pemahaman makna simbolik menunjukkan nilai vital dan nilai spritual sedangkan berdasarkan sumbernya menunjukkan nilai kasih sayang, keserasian hidup, dan nilai tanggung jawab. Nilai sosial dari pengalaman subjektif pembaca menunjukkan nilai vital dan spritual sedangkan berdasarkan sumbernya menunjukkan nilai kasih sayang, keserasian hidup, dan nilai tanggung jawab. Karya Fahrurraji Asmuni ini masih relevan dengan kehidupan masa kini dan dapat dijadikan pedoman bagi kita dalam menjalani kehidupan.Kata-kata kunci: sosiologi karya sastra, nilai sosial, hermeneutika, puisi, horizon